(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2021)
Law 14.026/2020 introduced significant changes to Law 11.445/2007, which establishes the national guidelines for basic sanitation in Brazil. The changes relating to the regionalized provision of basic sanitation services will be highlighted in this study. Article 3, item VI, of the Brazilian Basic Sanitation Framework, as amended by Law 14.026/2020, defines regionalized provision as: "[...] integrated provision of one or more components of public basic sanitation services in a given region whose territory covers more than one Municipality." The basic sanitation services are: a) drinking water supply; b) sewage disposal; c) urban cleaning and solid waste management; d) drainage and urban rainwater management. The law makes it possible for these services to be provided on a regional basis, i.e. municipalities can join technical and financial efforts to ensure that one or more of the components of the sanitation service are provided jointly to their respective populations. The purpose of the law is to prevent the risk of these services being poorly provided, or even not being provided for financial and/or technical reasons. The delicate fiscal situation of most Brazilian municipalities and the lack of technical resources to cope with the necessary expansion of basic sanitation services, which a significant part of the Brazilian population still cannot count on, are well known. The legislation seeks to overcome these difficulties by joining forces between the various municipal administrations interested in providing these services in partnership, making it possible to share resources and reduce costs, since the expansion of the universe of service users generates gains from economies of scale on the part of the provider(s).